Preparation of artificial latexes based on isoprene-styrene thermoplastic elastomers - I. A. Gritskova; O. I. Botova; R. O. Shitov; E. A. Grinfeld (Тонкие химические технологии)
The influence of solvent and surfactant (anionic and cationic) nature was discussed in this paper in order to find out the optimal conditions for the preparation of artificial latexes with different charges on the particle surface.